Copy number aberrations using multicolour fluorescence in situ hybridization (FISH) for prognostication in non‐muscle‐invasive bladder cancer (NIMBC). (26th July 2013) - Matsuyama, Hideyasu; Ikemoto, Kenzo; Eguchi, Satoshi; Oga, Atsunori; Kawauchi, Shigeto; Yamamoto, Yoshiaki; Kawai, Yoshihisa; Matsumoto, Hiroaki; Hara, Takahiko; Nagao, Kazuhiro; Sakano, Shigeru; Sasaki, Kohsuke
<x xml:space="preserve">Abstract</x> Objective To investigate if detection of copy number aberrations of chromosomes 3, 7, 9p21, and 17 using multicolour fluorescence in situ hybridization (FISH) predicts patient outcome in non‐muscle‐invasive bladder cancer (NMIBC). Patients and Methods In all, 118 bladder wash samples were prospectively collected from patients who underwent transurethral resection of bladder tumour (median age 50.5 years, male/female: 91/27, tumour grade 1/2/3: 18/52/42, stage pTis/Ta/T1: 8/62/42) from 2007 to 2010. The 118 samples were analysed using the UroVysion® kit to detect the copy numbers of chromosomes 3, 7, 9p21, and 17. The variant fraction (VF; the sum of the non‐modal copy number fraction of each chromosome) was defined as abnormal when the percentage was ≥16%. The percentage deletion of 9p21 (fraction of null or one copy number of the 9p21 locus) was defined as abnormal when the percentage was ≥12%. Maffezzini risk criteria were also analysed in our cohorts. Results There was recurrence in 57 (48.3%) patients and disease progression in 12 (10.1%), with a median follow‐up of 35.7 months. Multivariate analysis showed that the percentage 9p21 loss (>12%) was an independent prognostic factor for recurrence (P < 0.001, odds ratio [OR] 3.24, 95% confidence interval [CI] 1.85–5.62). For disease progression, tumour grade, positive urine cytology, concurrent carcinoma in situ, and a mean VF of >16% were significant prognostic factors in univariate analysis. In multivariate analysis, a mean VF of >16% was a prognostic factor for disease progression (P = 0.048, OR 6.07, 95% CI 1.02–57.45). Conclusions Multicolour‐FISH analysis using a commercially available kit could be a powerful tool not only for diagnosis, but also for prognostication in patients with NMIBC.